STRATEGI BERTAHAN HIDUP PETANI TADAH HUJAN DUSUN KOANYAR KLABANG BONDOWOSO - Murtiah, Murtiah; Mulyono, Joko (Jurnal ENTITAS SOSIOLOGI, 2019)
This research is a qualitative descriptive study which aims to describe and analyze the survival strategies of rainfed farmers in Koanyar Hamlet, Klabang Bondowoso. Rainfed lowland rice farming in Koanyar Hamlet is caused by a lack of water supply which has an impact on dry and dead plants. This means that farmers in overcoming crop failures prefer not to grow crops. The ownership of rainfed rice fields causes farmers to only be able to plant once a year so that it affects the income of farmers who are difficult to earn. Therefore, farmers make various ways to survive in difficult situations. The researcher in analyzing these problems uses a thinking framework from James C. Scott about the Survive Mechanism. The results of the study show that the survival strategies of farmers in Koanyar Hamlet namely saving, side work, having a patron, using a water suction machine, and choosing plants according to season. Keywords: Rainfed Rice Fields, Farmers, Survive Strategy